THE MAP OF METHODOLOGY AND TYPOLOGY OF GENDER EQUALITY INTERPRETATION IN INDONESIA - Thohiri, M. Kholid (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2021)
This article is the result of research on interpretations by several Muslim intellectuals on gender equality in Indonesia, namely M. Quraish Shihab, Masdar F. Mas'udi, Zaitunah Subhan, Nasaruddin Umar, Husein Muhammad. They are interpreters of the early generations of Indonesia who interpret the Qur'an about gender equality. There are many studies on the interpretation of gender equality in Indonesia, however the mapping of methodology and typology of several interpretations of gender equality in Indonesia does not yet exist. This type of research is a library with descriptive-analytic-typological form. the results of the research on the methodological map and typology of the interpretation of gender equality in Indonesia are:1. M. Quraish Shihab : forms and characters of bi al-ra'yi and scientific, methods and techniques of thematic interpretation of singular-plural and intertext, lughowi's interpretation style, integralistic typology. 2. Masdar Farid Mas'udi: forms and character bi al-ra'yi and socio-cultural, methods and techniques of singular thematic interpretation and intertext-criticism, fiqhi Interpretation style, divergent typology. 3. Zaitunah Subhan: forms and characteristics of bi al-ra'yi and socio-cultural interpretation, methods and techniques of singular and intertext-critical thematic interpretation, socio-anthropological interpretation, eclectic typology. 4. Nasaruddin Umar: forms and characteristics of bi al-ra'yi and semantics interpretation, methods and techniques for singular and intertext thematic interpretation, lughowi's lnterpretation style, eclectic typology. 5. Husein Muhammad: forms and characteristics of bi al-ra'yi and socio-cultural interpretations, methods and techniques of singular and intertext thematic interpretation, fiqhi interpretation style, and anticipatory typology